Pengaturan Hak Penguasaan Negara Atas Pertambangan Studi Perbandingan Konsepsi Kontrak Karya dengan Ijin Usaha Pertambangan - Mezak, Meray Hendrik (Pelita Harapan University, 2011)
Mining, as one of the revenue sources of the nation, could donate to the national income for the purpose of enhancing domestic welfare as stated in the Preamble of the 1945 Constitution. During the Old Regime, mining was regulated in Law No. 11 year 1969 concerning Basic Provisions of Mining. This law applied the Concept of âKontrak Karya,â but it has recently been replaced by Law No. 4 Year 2009 concerning Coal and Mineral Mining. The new law regulates that the operation of mining in any phase is conducted based on âIjin Usaha Pertambangan,â in order to accommodate the national interest, regional government, and society in the mining management in Indonesia.